(3QhVI GdCYdGe HefRdI GdYQHjI ef Ydhe GdESdGes - (3CHh YHO Gddg TeS GdOjf eMeO Hf Ydj Hf eMeO GdGUHMj GdCfOdSj, GHf GdGRQb,J (B896 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY efGQ GdYQHjI Ydi GdeOM hGdJYXje GdHMK GdChd ai JaSjQ GSe GdfMh dZI s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3bGd GHf GdefPQ cGf MGdc dGjhSY dCMO ai MdbJg hdG jQaYg jOY CMOge s
(3Cdag SfI (B875s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GddZIs